Psychophysical relationships between softness and pleasantness perceived by touch - Ng, Megan Hui Si (Nanyang Technological University, 2021)
The sense of touch is basic but vital. It allows us to perceive discriminative and affective sensations in relation to an object’s physical properties. While discriminative touch allows for the haptic recognition of objects, affective touch contributes hedonic properties such as pleasantness or unpleasantness. A previous study that investigated the psychophysical patterns of softness and pleasantness revealed that the higher the compliance (a physical correlate of softness) of deformable surfaces, the higher the perceived pleasantness. In extension, this study aims to find out if the previous results can be generalized to rigid surfaces, and if there is a range of compliance that corresponds to the maximum pleasantness. Two separate groups of participants were tasked to numerically estimate either the magnitude of softness or pleasantness after actively pressing down on both deformable and rigid surfaces. The results revealed that first, regardless of stimuli, perceived pleasantness increased up to the compliance of 1.4 mm/N. Second, the maximum perceived pleasantness was found to be between the range of 5 – 8 mm/N. These results suggest that first, surface deformability does not impede the perception of pleasantness against compliance and second, an optimal range of compliance corresponds to the highest pleasantness.